Enabling patient–physician continuity in Swedish primary care: the importance of a named GP. A registry-based observational study - Lina Maria Ellegård; Anders Anell; Gustav Kjellsson (BJGP Open)
Background: Continuity of care is important for patients with chronic conditions. Assigning patients to a named GP may increase continuity. Aim: To examine whether patients who were registered with a named GP at the onset of their first chronic disease had higher continuity of care at subsequent visits than patients who were only registered at a practice. Design & setting: Registry-based observational study in Skåne County, Sweden. The study population included 66 063 patients registered at the same practice at least 1 year before the onset of their first chronic condition between 2009 and 2015. Method: We compared patients registered with a named GP with patients only registered at a practice over a 4-year follow-up period. The primary outcome was the usual provider of care (UPC) index for all visits and for visits related to the chronic disease. Secondary outcomes were the number of GP, nurse, and out-of-hours visits; emergency department visits; hospital admissions; and mortality. We used linear regression models, adjusted for patient characteristics (using entropy balancing weights) and for practice-level fixed effects, to compare the UPC between those registered with a named GP and those who were not. Results: Patients with a named GP at onset of their condition had a UPC that was 3–4 percentage points higher than patients who did not have a named GP, but the difference decreased and was not statistically significant after adjusting for patient and practice characteristics. Patients with a named GP made more visits, although not specifically for the chronic condition. There were no statistically significant differences for the other outcomes. Conclusion: Patient registration with a GP at diagnosis of their first chronic condition does not demonstrate higher continuity of care at subsequent GP visits and is not linked to other relevant outcomes for patients.